Quality management of biosampling and data collection from women at different stages of pregnancy for the search for early biomarkers of preterm birth: predicting errors and risk management - O. V. Pachulia; R. A. Illarionov; E. S. Vashukova; N. A. Yurkina; M. G. Butenko; T. B. Postnikova; O. N. Bespalova; A. S. Glotov (Кардиоваскулярная терапия и профилактика)
The main condition for ensuring effective sampling for creating a bioresource collection is quality management, which implies careful planning and predicting errors at all stages. Risk management of samples and data loss is ensured by correct logistics, circumspect algorithms and standardization of processes. Features of the logistic processes for creating biosample collection from the pregnant women are described in this article.